The Gülen Movement and Surviving in Exile: The case of Australia. (2nd January 2018) - Tittensor, David
ABSTRACT: In 2010, cracks began to emerge in the tacit alliance between the ruling Adalet ve Kalkınma Partisi (Justice and Development Party in Turkey, AK Party) and the Gülen Movement (GM) and escalated into an all-out struggle in 2013. Following the failed 15 July coup in 2016, Erdoğan sought to eradicate the movement completely, seizing 11 billion in GM assets and purging over 150, 000 people from all sectors, public and private. However, Erdoğan is aware that victory at home will not defeat the GM, as it operates in around 160 countries. As a result, he has put pressure on many nations to crackdown on the GM and their activities. While this approach has had some success in the Gulf Countries, Africa and South East Asia, it has been largely ineffective in the West, and Australia is no exception. Therefore, this paper will explore the Australian case and look at the factors behind continued local support for the GM. It will argue that the GM has made excellent use of opportunity spaces and structures in both academia and the NGO sector where it has been able to control its own narrative and engage effectively in cultural diplomacy, particularly amongst the political class.